PEMBELAJARAN TEMATIK MELALUI PENDEKATAN SAINTIFIK BERBASIS QUANTUM TEACHING TANDUR DAN MEDIA AUDIO VISUAL - Lusa, Herman (ATTA`DIB, 2015)
Thematic Learning in the field has not practiced optimally. This research found that still many implementations of teacher-centered in teaching learning process. Students tend to be passive and only learn from the text book. So, thematic learning innovation is needed to increase the learning activity. From thematic scientific approach through the implementation of quantum learning model of teaching that applies the concept TANDUR (Tanamkan, Alami, Namai, Demonstrasikan, Ulangi, dan Rayakan) make student-centered learning The use of audio media in the form of children's songs, instruments, and pictures help students learning with fun, so that process activities and thematic learning outcomes and student skills in creative thinking will increase.